Paratracheal air cysts; a rare cause of recurrent hemoptysis - Rampradeep, Rishab; G., Prasanth; V., Gangadharan (International Journal of Advances in Medicine, 2023)
Paratracheal air cysts (PTACs) refer to small collections of air, present at the level of the thoracic inlet, adjacent to the trachea. PTACs encompass a variety of pathological entities and are usually encountered incidentally on computed tomography (CT) of the chest. Clinically, most patients remain asymptomatic; while a minority, may be associated with cough, dyspnea and hemoptysis probably as a result of pooled secretions and secondary infections. We report one such case of recurrent hemoptysis in a 30-year-old male, as a result of a right paratracheal air cyst.